Liability and peaceful, civil space activities at national, regional and international levels : selected legal issues - O'Brien, Zeldine Niamh (Trinity College (Dublin, Ireland). School of Law, 2010)
The thesis "Liability and Peaceful Space Activities: Selected Legal Issues at National, Regional and International Levels" defines space activities by reference to the historical development of the space industry, its current and future prospects as well as the development of law. It assesses the choice between functionalism and spatialism in light of increased private commercial exploitation of space. There are several trends evident - first increased private commercialisation of space activities, second, the development of a private space transportation of persons industry and third, a movement away from binding regulation on space issues from COPUOS to soft law measures. It is in this context that the current regulation of liability and ancillary issues are examined. The ancillary issues include sovereignty, ownership and jurisdiction in outer space as well as insurance and are analysed in light of these trends. This examination is conducted at three levels - national, regional (European) and international.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin